Construction and Characterization of Bivalent Shigella flexneri 2a Vaccine Strains SC608(pCFAI) and SC608(pCFAI/LTB) That Express Antigens from Enterotoxigenic Escherichia coli - Ranallo, Ryan T. (American Society for Microbiology, 2005)
An invasive strain of Shigella flexneri 2a (SC608) has been developed as a vector for the expression and delivery of heterologous antigens. SC608 is an aspartate semialdehyde dehydrogenase (asd) derivative of SC602 (icsA iuc), a well-characterized live attenuated vaccine strain which has undergone several clinical trials in human volunteers. When administered orally at a single 10(4) (CFU) dose, SC602 is both immunogenic and efficacious against shigellosis. Using asd-based plasmid vectors, we designed SC608 to express the enterotoxigenic Escherichia coli (ETEC) fimbrial subunit CfaB (CFA/I structural subunit) alone or in combination with the E. coli B subunit of heat-labile enterotoxin (LTB). The expression of each heterologous protein in SC608 was verified by immunoblot analysis. Each strain was comparable to the parent strain, SC602, in a HeLa cell invasion assay. After intranasal immunizations of guinea pigs, serum and mucosal immune responses were detected against both Shigella lipopolysaccharide and heterologous ETEC antigens by enzyme-linked immunosorbent assay and ELISPOT analysis. All immunized animals were subsequently protected against a challenge with wild-type S. flexneri 2a in a keratoconjunctivitis Sereny test. Serum antibodies generated against LTB and CfaB demonstrated antitoxin and agglutination activities, respectively. These results suggest that CfaB and LTB expressed in SC608 retain important conformational epitopes that are required for the generation of antibodies that have functional activities. These initial experiments demonstrate that a fully invasive Shigella vaccine strain can be engineered to deliver antigens from other diarrheal pathogens.